DOMESTIC WASTEWATER PURIFICATION IN UPFLOW BIOFILM SYSTEM WITH DIFFUSED AERATION - A.Mesdaghinia (Tehran University of Medical Sciences, 1984)
The objective of this research was to conduct a bench scale study of fixed activated sludge treating domestic sewage. Two different units employing diffused aeration with plastic and aluminum media were studied in four separate phases. Data indicated that the system could produce a high quality effluent without any requirements for sludge recycling through the system. Suspended solids concentrations of 3-6 mg/1, BOD5 concentrations of 4-12 mg/1 and COD concentrations of 35-45 mg/1 were found in the effluent with wastewater retentions ranging from 3-15 hours, whereas an indication of nitrification was observed in higher detention periods. As far as the type of media was concerned, the plastic and aluminum media did not differ significantly once the microbes had grown on the media.